Infrared laser based contacting of bar-wound windings in the field of electric drives production - Gläßel, Tobias; Baat, Florian; Schwinghammer, Daniel; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (Procedia CIRP, Volume 74, 2018)
Driven by electric mobility innovative winding methods increasing the copper fill ratio and thus the power density of electrical drives gain in importance. Compared to conventional windings, bar-wound windings based on rectangular cross sections besides optimized copper fill ratios also offer advantages in terms of automated production. Because of the high number of joints necessary for the manufacturing of the winding, contacting efforts increase significantly wherefore the process of laser welding, due to its short process times and high reproducibility shows potentials to realize the process step. This paper examines the most important interactions within the process of laser welding of insulated copper wires with rectangular cross sections in the context of electric drives production. Besides workpiece specific factors, the focus is set on process parameters, beam guidance strategies and specific quality requirements. For this purpose, a parameter study based on design of experiments is executed in which suitable measuring technologies are used to quantify the properties of the samples. <br
Keywords: laser beam welding; infrared lasers; insulated copper conductors; hairpin windings; electrical contacts